2008
DOI: 10.1016/j.jebo.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Does culture influence asset managers’ views and behavior?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(55 citation statements)
references
References 60 publications
2
51
0
2
Order By: Relevance
“…Less experience of European companies with the use of RM might lead to the listing of more risks. A more risk-seeking and more innovation-friendly attitude within North America (see, for example, Weber and Hsee, 1998;Beckmann et al, 2008;Martin et al, 2009) might lead to a different perception of existing risks. Figure 9: Benefits named by North American versus European companies.…”
Section: Benefits and Risks Of Rmmentioning
confidence: 99%
“…Less experience of European companies with the use of RM might lead to the listing of more risks. A more risk-seeking and more innovation-friendly attitude within North America (see, for example, Weber and Hsee, 1998;Beckmann et al, 2008;Martin et al, 2009) might lead to a different perception of existing risks. Figure 9: Benefits named by North American versus European companies.…”
Section: Benefits and Risks Of Rmmentioning
confidence: 99%
“…Overall, effort was taken to ensure the right "properties of the situation" (Levitt and 8 The international survey underlying this research is the basis of a larger research project and has been used in other directions as well. Beckmann et al (2008), for example, examine cultural differences between fund managers. 9 The language of the survey was English in the U.S. and Thailand, German in Germany, German and French in Switzerland and Italian in Italy.…”
mentioning
confidence: 99%
“…Several studies found that cultures and beliefs might affect investment decisions. Beckmann et al (2007) found that in asset management there were country-specific differences that could hardly be explained by capital market theory but that were consistent with cultural influences on views and behaviors instead. This finding was supported by conclusion reached by Statman (2008) who concluded that the collective set of common experiences that people of the same culture share would influence their cognitive and emotional approaches to investing.…”
Section: Behavioral Finance and Superstitionsmentioning
confidence: 59%